The oncocytic subtype is genetically distinct from other pancreatic intraductal papillary mucinous neoplasm subtypes - Basturk, Olca (Mod Pathol, 2016)
In 2010, the World Health Organization reclassified the entity originally described as intraductal oncocytic papillary neoplasm as the ‘oncocytic subtype’ of intraductal papillary mucinous neoplasm. Although several key molecular alterations of other intraductal papillary mucinous neoplasm subtypes have been discovered, including common mutations in KRAS, GNAS, and RNF3, those of oncocytic subtype have not been well characterized. We analyzed 11 pancreatic ‘oncocytic subtype’ of intraductal papillary mucinous neoplasms. Nine pancreatic ‘oncocytic subtype’ of intraductal papillary mucinous neoplasms uniformly exhibited typical entity-defining morphology of arborizing papillae lined by layers of cells with oncocytic cytoplasm, prominent, nucleoli, and intraepithelial lumina. The remaining two were atypical. One lacked the arborizing papilla and had flat oncocytic epithelium only; the other one had focal oncocytic epithelium in a background of predominantly intestinal subtype intraductal papillary mucinous neoplasm. Different components of this case were analyzed separately. Formalin-fixed, paraffin-embedded specimens of all cases were microdissected and subjected to high-depth-targeted next-generation sequencing for a panel of 300 key cancer-associated genes in a platform that enabled the identification of sequence mutations, copy number alterations, and select structural rearrangements involving all targeted genes. Fresh frozen specimens of two cases were also subjected to whole-genome sequencing. For the nine typical pancreatic ‘oncocytic subtype’ of intraductal papillary mucinous neoplasms, the number of mutations per case, identified by next-generation sequencing, ranged from 1 to 10 (median = 4). None of these cases had KRAS or GNAS mutations and only one had both RNF43 and PIK3R1 mutations. ARHGAP26, ASXL1, EPHA8, and ERBB4 genes were somatically altered in more than one of these typical ‘oncocytic subtype’ of intraductal papillary mucinous neoplasms but not in the other two atypical ones. In the neoplasm with flat oncocytic epithelium, the only mutated gene was KRAS. All components of the intestinal subtype intraductal papillary mucinous neoplasms with focal oncocytic epithelium manifested TP53, GNAS, and RNF43 mutations. In conclusion, this study elucidates that ‘oncocytic subtype’ of intraductal papillary mucinous neoplasm is not only morphologically distinct but also genetically distinct from other intraductal papillary mucinous neoplasm subtypes. Considering that now its biologic behavior is also being found to be different than other intraductal papillary mucinous neoplasm subtypes, ‘oncocytic subtype’ of intraductal papillary mucinous neoplasm warrants being recognized separately.